Synergistic Effects of Tuna and Moringa Leaf Nuggets on Maternal Nutritional Status: A Comparative Study - Sesca D Solang; Freike Lumy; Yohanis Tomastola; Nonce Nova Legi; Lorrien Grace Runtu; I Ketut Harapan (Media Publikasi Cendekia Indonesia, 2026)
Chronic Energy Deficiency (CED) and anemia in pregnant women are significant nutritional challenges that negatively impact maternal and fetal health outcomes. This study evaluated the effectiveness of a local food-based intervention using nuggets made from tuna fish and moringa leaves to address these issues. We conducted a quasi-experimental study with a pretest-posttest control group design involving 60 pregnant women in the Kema Community Health Center working area, North Minahasa. The subjects were divided into two groups: an intervention group receiving tuna-moringa nuggets (n=30) and a control group receiving only tuna nuggets (n=30). Both groups consumed four nuggets daily for 30 days. We measured Mid-Upper Arm Circumference (MUAC) and hemoglobin (Hb) levels before and after the intervention. Data analysis involved paired t-tests for within-group changes and independent t-tests for between-group comparisons. The results showed significant increases in mean MUAC and Hb levels in both groups (p < 0.05). Both the intervention and control groups exhibited an identical mean increase in MUAC of 1.1 cm from baseline, suggesting comparable physical growth in both study arms. However, the intervention group demonstrated a significantly higher mean increase (delta) in Hb levels (2.11 g/dL) compared to the control group (1.17 g/dL) (p < 0.05). In conclusion, while both nugget types support nutritional improvement, the tuna-moringa nuggets are more effective in elevatingthe hemoglobin levels of pregnant women. This intervention serves as a practical, nutrient-dense strategy to mitigate CED and anemia using accessible local resources.